PENGARUH MEDIA SOSIAL TERHADAP MINAT BELI KONSUMEN DI KOTA MEDAN - Novitasari Novitasari; Nabeel Al Fattah Yusuf; Agnes Monika Gulo; Rona Malum Berutu (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study aims to identify the role of social media in driving consumer purchasing interest in Medan. The rapid development of digital technology has transformed social media into a highly influential marketing tool for businesses. The study used quantitative methods with data collection through a Google Form questionnaire, which successfully obtained 35 respondents. The findings indicate that high frequency of social media use, particularly on platforms that emphasize visual content like TikTok and Instagram, contributes strongly to increased purchasing interest. Factors such as product visual appearance, user reviews, and the influence of influencers are key drivers of consumer interest. Most respondents also admitted to having made a purchase after seeing a promotion on social media and found the product information presented very helpful in making a choice. Social media has been proven to play a significant role in shaping purchasing interest, especially among the younger generation in Medan.